The regulatory, evaluation, pricing and reimbursement pathway for medicines in the UK: combining innovation and access - Adriana M. IVAMA-BRUMMELL; Pilar PINILLA-DOMINGUEZ; Aline N. BIZ (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2022)
The United Kingdom has universal healthcare systems, the National Health System (NHS), in its four nations, with healthcare services provided free of charge at the point of delivery. Approximately 10.5% of the UK population has voluntary supplementary private health insurance. While the provision of inpatient medicines is free of charge, medicines provided in the outpatient setting have a dispensing fee in some of the nations, such as the case of England (co-payment). The UK marketing authorisation process is called product licensing and is overseen by the Medicines and Healthcare Products Regulatory Agency (MHRA). There are different licensing routes based on the intended market for launch. MHRA also offers early access schemes and pathways for products targeting unmet medical needs and promising technologies, that aim to accelerate and facilitate market and patient access to products in the UK. These schemes include the option for companies to engage early with regulators and other system partners such as health technology assessment (HTA) agencies. As soon as the technology is authorised, it is available at a list price. Prices for medicines are regulated in legislation and in schemes agreed between the industry association and the Department of Health and Social Care (DHSC). The prices for the NHS are negotiated between the government and the companies. Routine funding decisions in the NHS are guided by HTA evaluations informed by agencies such as the National Institute for Health and Care Excellence (NICE) in England, the Scottish Medicines Consortium (SMC) in Scotland, and the All Wales Medicines Strategy Group (AWMSG) in Wales. Many medicines and other technologies are subject to price negotiations in the NHS, sometimes with confidential price agreements. The NHS in England is legally mandated to routinely fund technologies recommended by NICE that have been evaluated by some of its programmes. The other UK nations have similar arrangements or recognise decisions made in England. The role and contribution of NICE and other HTA agencies in ensuring value for money and evidence-based decision making is well recognised worldwide.